Conscience and Coercion: Ahmadi Muslims and Orthodoxy in Pakistan - Teekoy, Mathew C (Journal of Dharma, 1992)
Antonio R. Gualtieri, Conscience and Coercion; Ahmadi Muslims and Orthodoxy in Pakistan, Montreal: Guernica Publications, 1 989, pp. 1 26